2021
DOI: 10.1002/smll.202102047
|View full text |Cite
|
Sign up to set email alerts
|

CdSe 1D/2D Mixed‐Dimensional Heterostructures: Curvature‐Complementary Self‐Assembly for Enhanced Visible‐Light Photocatalysis

Abstract: Mixed‐dimensional heterostructures (MDHs), which combine nanomaterials of different dimensionalities deliver on the promise to bypass intrinsic limitations of a given low‐dimensional material. Here, a strategy to engineer MDHs between two low‐dimensional materials by curvature‐complementary self‐assembly is described. CdSe nanotubes rolled from 2D nanosheets and 1D CdSe nanorods, with negative and positive curvatures, respectively, are selected to illustrate complementary curvature self‐assembly. The assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…CdSe NRs were synthesized based on a previous report 39 , 41 . CdSe NRs capped with TOP, TOPO, TDPA, and TBP were synthesized using a Schlenk-line.…”
Section: Methodsmentioning
confidence: 99%
“…CdSe NRs were synthesized based on a previous report 39 , 41 . CdSe NRs capped with TOP, TOPO, TDPA, and TBP were synthesized using a Schlenk-line.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, imparting porosity, especially for hierarchical pores ranging from micropores to mesopores, into the QDs solids would overcome the gas diffusion-limited issue. Packing of QDs into non-close-packed (NCP) structure in confined medium could be one of the possible solutions, but it requires precise design of colloidal building blocks 29 , 30 . The development of reticular chemistry enables the synthesis of metal-organic frameworks (MOFs), covalent-organic frameworks (COFs), and porous organic cages (POCs), which potentially provides diversified yet robust porous scaffolds hosting the QDs solids 31 35 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wei et all. assembled two-site nanosheets with negative curvature and one-dimensional CdSe nanorods with positive curvature to adjust the band gap structure of CdSe to form a hybrid dimensional heterojunction material . Khalaf et al successfully grew CdSe nanocrystals on glass substrates by plasma sputtering with film thicknesses ranging from 350 to 600 nm and found that the optical band gap decreases with increasing sample size …”
Section: Introductionmentioning
confidence: 99%